2012
DOI: 10.1177/0022034512443068
|View full text |Cite
|
Sign up to set email alerts
|

Dentin-cement Interfacial Interaction

Abstract: The interfacial properties of a new calcium-silicate-based coronal restorative material (Biodentine™) and a glass-ionomer cement (GIC) with dentin have been studied by confocal laser scanning microscopy (CLSM), scanning electron microscopy (SEM), micro-Raman spectroscopy, and two-photon auto-fluorescence and second-harmonic-generation (SHG) imaging. Results indicate the formation of tag-like structures alongside an interfacial layer called the "mineral infiltration zone", where the alkaline caustic effect of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
110
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(137 citation statements)
references
References 26 publications
2
110
1
Order By: Relevance
“…It also allows better penetration within dentin tubules for mechanical retention. 27,28 Although all three cements exhibited similar bond strength in the present study, the failure mode of Biodentine was different with a higher incidence of cohesive failure. This suggests that Biodentine may be used as an alternative to MTA because of its improved stability at the filling site.…”
Section: Discussionmentioning
confidence: 47%
“…It also allows better penetration within dentin tubules for mechanical retention. 27,28 Although all three cements exhibited similar bond strength in the present study, the failure mode of Biodentine was different with a higher incidence of cohesive failure. This suggests that Biodentine may be used as an alternative to MTA because of its improved stability at the filling site.…”
Section: Discussionmentioning
confidence: 47%
“…During the 72 hours of application of Biodentine ® on the culture plate, the modifications that occurred underlined the positive trend of mitochondrial activity. Considering the interface between dentin and Biodentine ® with confocal microscopy, an increased content of carbonate and the creation of a hybrid layer was demonstrated (43,44). Furthermore, Biodentine ® showed the ability to induce the differentiation of odontoblasts starting from pulp progenitor cells, forming a mineralizing matrix with the characteristics of dentin (45).…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, the different particle sizes of MTA and Biodentine may affect their penetration into the dentinal tubules, with consequences to displacement resistance. Atmeh et al 18 demonstrated that Ca-Si cements facilitate the permeation of Ca and OH ions into the dentine, due to their caustic effect. It can be assumed that the improved ability to release remineralizing Ca and OH ions by Biodentine 19 is responsible for the improved formation of apatite at the interface 19,20 , and for micromechanical anchorage 21 .…”
Section: Discussionmentioning
confidence: 99%